In Vitro Metabolism of E2, G2: Novel Bile Acid-Coupling Camptothecin Analogues, in Rat Liver Microsomes - Zhang, Xiangli; Shen, Qin; Wang, Yi; Zhou, Leilei; Weng, Qi; Li, Qingyong (Recent Patents on Anti-Cancer Drug Discovery, 2021)
Background: E2 (Camptothecin - 20 (S) - O- glycine - deoxycholic acid), and G2 (Camptothecin - 20 (S) - O - acetate - deoxycholic acid) are two novel bile acid-derived camptothecin analogues, modified deoxycholic acid at 20-position of CPT(camptothecin) with greater anticancer activity and lower systematic toxicity in vivo. Objective: We aimed to investigate the metabolism of E2 and G2 by Rat Liver Microsomes (RLM). Methods: Phase I and Phase II metabolism of E2 and G2 in rat liver microsomes were performed, respectively, and the mixed incubation of phase I and phase II metabolism of E2 and G2 was also processed. Metabolites were identified by liquid chromatographic/mass spectrometry. Results: The results showed that phase I metabolism was the major biotransformation route for both E2 and G2. The isoenzyme involved in their metabolism had some difference. The intrinsic clearance of G2 was 174.7 mL/min. mg protein, more than three times that of E2 (51.3 mL/min . mg protein), indicating a greater metabolism stability of E2. 10 metabolites of E2 and 14 metabolites of G2 were detected, including phase I metabolites (mainly via hydroxylations and hydrolysis) and their further glucuronidation products. Conclusion: These findings suggested that E2 and G2 have similar biotransformation pathways except for some differences in the hydrolysis ability of the ester bond and amino bond from the parent compounds, which may result in the diversity of their metabolism stability and responsible CYPs(Cytochrome P450 proteins).
Keywords: liver microsomes